The x is a placeholder for some currently unknown number. Let's say that number was 10. So we replace x with 10 to get 10-3 = 12. That statement is false because 10-3 is actually 7. What you can do is keep guessing until you get the right answer.
A much better approach is to undo what is happening to x. We have x and we subtract off 3 to get 12. Following this in reverse, we need to add 3 to both sides so that x is isolated.
x-3 = 12
x-3+3 = 12+3
x = 15
Let's replace x with 15 and see if the equation is true
x - 3 = 12
15 - 3 = 12
12 = 12
Sure enough we get the right answer.
The idea of adding 3 to both sides is possible through the additive property of equality (if a = b, then a+c = b+c)
==========================================
In summary, I added 3 to both sides using the additive property of equality. Doing this isolated x to get x = 15.
Solve for x
(x-4)(x - 4) = 0
Answer:
x=4
Step-by-step explanation:
Answer:
X=4
Step-by-step explanation:
(x-4)(x-4)=0
if x=4 then 4-4=0
0^(x-4)=
x-4=0
0^0=0
Which expression is equivalent to 6x2– 19x – 55?
Answer:
( 6x + 11 ) ( x - 5 )
Step-by-step explanation:
Let
6x2 - 19x - 55 = 0
6x2 - (30-11)x - 55 = 0
6x2 - 30x + 11x - 55 = 0
6x ( x - 5 ) + 11 ( x - 5 ) = 0
( 6x + 11 ) ( x - 5 ) = 0
Therefore, ( 6x + 11 ) ( x - 5 ) = 6x2 - 19x - 55
What is the quotient of -13/8 divided by -1/4
Answer:
0.40625
Step-by-step explanation:
Answer:
The answer is 13/2
Step-by-step explanation:
given the two Fibonacci numbers below, which number would follow? F(14) = 377 and F(15) = 610
Answer:
987.
Step-by-step explanation:
The terms in a Fibonacci series are obtained form the sum of the previous 2 terms. So the next number F(16) = 377 + 610 = 987.
APEX ANSWER: 987
Step-by-step explanation:
377 + 610 = 987
Hello
I will mark you as a brainliest
Please answer my question.....
Solve the following equation:-
6+5 (a-1) = 30
Answer:
29/5 or 5.8
Step-by-step explanation:
6+5(a−1)=30
first it would be good to distribute:
6+5(a-1)=30 -> 6+(5)(a)+(5)(−1)=30 which simplifies to 6+5a+−5=30
at this point it is best to rearrange:
(5a)+(6+−5)=30 which simplifies to 5a+1=30
from then on its a matter of doing opposite operation. at my school we would call this the "equality" method. what you do to one side you do the other.
Observe:
5a+1=30
-1 -1
5a=29
5a/5=29/5
a=29/5 (in decimal it would be like 5.8)
I hope this is helpful!
I need help!!!!
Which represents the inverse of the function f(x)=4x?
Answer:
[tex]h(x)=\frac{1}{4}x[/tex].
Step-by-step explanation:
The inverse is basically you just swapping x and y. People want to solve it for y to make it a function of x.
[tex]y=4x[/tex]
Swap x and y:
[tex]x=4y[/tex]
Now solve for y by dividing y on both sides:
[tex]\frac{x}{4}=y[/tex]
[tex]\frac{1}{4}x=y[/tex]
[tex]y=\frac{1}{4}x[/tex].
PLEASE HURRY
WILL GIVE BRAINLIEST
What is the slope of the line represented by the equation y = x – 3? –3 3
Answer:
None of then, the slope is 1
Step-by-step explanation:
We have to use the general equation for lines, that is:
[tex]y=mx+b[/tex]
where 'm' is the slope (by comparison)
So, we only need to compare your equation ([tex]y=x-3[/tex]) with the general one.
We can see that m=1, b=-3
So our slope turns out to be equals to 1
Points C, D, and G lie on plane X. Points E and F lie on plane Y.Which statements are true? Select three options.
Answer:
2nd , 3rd, & 4th
Step-by-step explanation:
Find the length of KB¯¯¯¯¯¯¯¯+AK¯¯¯¯¯¯¯¯.
A. 28
B. 33
C. 21
D. 35
Intersecting chord rule:
DK x KB = AK x CK
12 x 4x+1 = 14 x 3+3x
Simplify:
48x +12 = 42x +42
Subtract 12 from each side:
48x = 42x + 30
Subtract 42x from each side:
6x = 30
Divide both sides by 6:
x = 5
Now find the length of KB: 4x +1 = 4(5) +1 = 20 +1 = 21
Now add KB and AK:
21 + 14 = 35
The answer is D. 35
The required length of KB(21) + AK(14) is 35. Option D is correct.
The figure is given,
where AK = 14. DK = 12, KB = 4x+1 and KC =3+3x.
KB + AK to be determined.
The ratio can be defined as the relativeness of the fraction of one quantity towards others.
Here,
The ratio of AK: DK = KB:KC
[tex]14/12= 4x+1/3+3x\\14*(3+3x) = 12*(4x+1)\\2+42x = 48x+12\\42-12=48x-42x\\6x= 30\\x = 5[/tex]
Now,
= KA + KB
= 14 + 4x+1
= 14+ 4(5)+1
= 35
Thus, the required length of KB + AK is 35.
Learn more about ratios here:
brainly.com/question/13419413
#SPJ5
The system of equations y=-1/2x+4 and y = 2x – 1 is shown on the graph below. According to the graph, what is the solution to this system of equations?
A. (2, 3)
B. (3, 2)
C. (–1, 4)
D. (4, –1)
Answer: You can use a graphing calculator in the future
(2,3)
A
Answer: A(2,3)
Step-by-step explanation:
To solve the system of equations;
y=-1/2x+4 and y = 2x – 1
y=-1/2x+4 ----------(1)
y = 2x – 1 -----------(2)
Lets substitute equation 2 in equation 1
2x - 1 = -1/2x+4
Collect like term
(We move the x variables from the right -hand side of the equation to the right-hand side of the equation to the right-hand-side of the equation and then move the constants to the right-hand side of the equation)
2x + 1/2x = 4 + 1
5x/2 = 5
To get the value of x, we will multiply both-side of the equation by 2/5
5x/2 × 2/5 = 5 × 2/5
(On the left-hand side of the equation, the 5/2 will cancel out the 2/5 leaving us with x and on the right-hand side of the equation 5 will cancel out 5 leaving us with 2)
x = 2
Substitute x =2 in equation (2)
y = 2x - 1
y = 2(2) - 1
y = 4 -1
y =3
The solution to the system of the equations is x=2 and y=3
Therefore the answer is A(2,3)
the algebraic expression for "the quotient of 51 and x" is?
Answer:
51/x
The first number/ variable always goes on top
Should it be facing left or right ?
Answer:
Facing Right
Step-by-step explanation:
Given inequalities are:
4-x≤-1
Subtracting 4 from both sides
4-x-4≤-1-4
-x≤-5
Multiplying both sides with -1. Multiplying with a negative number changes the sign of the inequality
So,
x≥5
Second Inequality:
2+3x≥17
Subtracting 2 from both sides
2+3x-2≥17-2
3x≥15
Dividing both sides by 3
x≥5
Union of both solutions:
x≥5 ∩ x≥5
=> x≥5
Hence the solution will be facing right on the number line towards all numbers greater than or equals to 5 ..
Write an equation of the direct variation that includes the point (6,-2)
Answer:
[tex]y = - \frac{1}{3}x[/tex]
Step-by-step explanation:
The equation of a direct variation is generally written as:
[tex]y = mx[/tex]
Where m is the slope of the equation of the direct variation line.
We want a direct variation equation that contains (6,-2).
We substitute the x=6 and y=-2 to find m.
[tex] - 2 = 6m[/tex]
Divide both sides by 6.
[tex] \frac{ - 2}{ 6} = \frac{6m}{ 6} [/tex]
[tex] - \frac{1}{3} = m[/tex]
The required equation is
[tex]y = - \frac{1}{3}x[/tex]
The equation of the direct variation that includes the point (6,-2) is y = -1/3x, calculated by substituting the point into the formula y = kx and solving for the constant of variation k.
Explanation:The subject of this question is mathematical, focusing on direct variation - a specific type of relationship between two variables where one variable is a constant multiple of the other. In this case, the student is given the point (6,-2) on the graph of this relationship. With direct variation, the formula is typically written as y = kx, where k is the constant of variation.
For this particular question, we use the point (6,-2) and substitute x = 6 and y = -2 into the formula to find the constant of variation, i.e. -2 = k * 6. Solving for k, we get k = -2/6 = -1/3. Plugging this k back into y = kx gives us our equation of the direct variation: y = -1/3x.
Learn more about Direct Variation here:https://brainly.com/question/9775007
#SPJ3
SOMEONE PLEASE HELP ME WITH THIS QUESTION!!!!!
Which expressions are equivalent to -7+3(-4e-3)?
Choose all answers that apply:
(Choice A)
-4(3e+4)
(Choice B)
12e
(Choice C)
None of the above
Answer:
(Choice A)
-4(3e + 4)
Step-by-step explanation:
This is the only answer that makes sense:
-7 - 12e - 9 [Distribute the 3 amongst all the other terms in parentheses]
Then you combine like-terms:
-16 - 12e
Finally, you factor out the Greatest Common Factor [GCF]:
-4[4 + 3e]
12e is NOT an option, so you are left with (Choice A).
I am joyous to assist you anytime.
At East Middle School, there are 58 left-handed students and 609 right-handed students. The numbers of left- and right-handed students at West Junior High are proportional to the numbers at East Middle School. Which of the following could be the numbers of left-handed and right-handed students at West Junior High?
Choose 2 answers:
A= left-handed: 42
Right-handed: 483
B= lef-handed: 28
Right-handed: 378
C= left-handed: 48
Right-handed: 504
D= left-handed: 56
Right-handed: 560
E: left-handed: 30
Right-handed: 315
Answer:
C. Left-handed: 48, Right-handed: 504
D. Left-handed: 30, Right-handed: 315
Step-by-step explanation:
We are given that there are 58 left-handed students and 609 right-handed students at East Middle School and these numbers of students are proportional to the number of left and right handed students at East Middle School.
Given the above information, we are are to determine which two options could be the the numbers of left-handed and right-handed students at West Junior High.
Ratio of right handed to left handed students at East Middle School = [tex]\frac{609}{58} = 10.5[/tex]
Checking for ratios of the given options:
A. [tex]\frac{483}{42} =11.5[/tex]
B. [tex]\frac{378}{28} =13.5[/tex]
C. [tex]\frac{504}{48} =10.5[/tex]
D. [tex]\frac{560}{56} =10[/tex]
E. [tex]\frac{315}{30} =10.5[/tex]
Therefore, the possible numbers of left-handed and right-handed students at West Junior High could be C. Left-handed: 48, Right-handed: 504 and D. Left-handed: 30, Right-handed: 315.
Answer:
OPTION C.
OPTION E.
Step-by-step explanation:
A relationship is proportional if the ratio between the variables is always the same.
In this case we know that the numbers of left- and right-handed students at West Junior High are proportional to the numbers at East Middle School and there are 58 left-handed students and 609 right-handed students at East Middle School. Therefore, the ratio is:
[tex]ratio=\frac{58}{609}=\frac{2}{21}[/tex]
So, we can check the ratio in each option to know which has ratio [tex]\frac{2}{21}[/tex]:
OPTION A:
[tex]\frac{42}{483}=\frac{2}{23}[/tex]
OPTION B:
[tex]\frac{28}{378}=\frac{2}{27}[/tex]
OPTION C:
[tex]\frac{48}{504}=\frac{2}{21}[/tex]
OPTION D:
[tex]\frac{56}{560}=\frac{1}{10}[/tex]
OPTION E:
[tex]\frac{30}{315}=\frac{2}{21}[/tex]
Therefore, you can observe that the numbers of left-handed and right-handed students at West Junior High could be:
[tex]Left-handed: 48\\Right-handed: 504\\\\\\Left-handed: 30\\Right-handed: 315[/tex]
A pair of parallel lines is cut by a transversal, as shown below:
Answer:
I don't know what your choices are but they are alternate interior angles. Alternate interior angles are congruent.
Step-by-step explanation:
Alternate interior angles are the angles at the different intersection along the transversal that are on opposite sides of the transversal and inside the parallel lines.
This is exactly what you have here, alternate interior angles are congruent when the the lines are parallel.
There are also alternate exterior. These are at the different intersections along the trasversal that are opposite sides of the transversal but outside the parallel lines.
There is also corresponding angles. I like to call these the copy and paste angles because when you copy one intersection and paste it over the other, the corresponding angles will be the ones that lay on top of each other.
There are also same-side interior angles. There are inside and on the same side of the transveral at the different intersections. These angles add up to be 180 degrees when the transversal cuts through parallel lines.
Answer:
The answer is ---> x = y
Step-by-step explanation:
Here are the answer choices.
x = y x = 180° − y y = 180° − x x = 2yI got it correct, so this was the answer
Find the value when x=2and y=3 x^-3y^-3
Answer:
4/27
Step-by-step explanation:
x^-3y^-3
Let x=2 and y=3
2^ (2) (3)^-3
2^2 * 1/3^3
4/27
241,389.613 which digit is in the hundred millons place
Answer:
241,389.613
Step-by-step explanation:
The first 1 is in the hundred millons place.
Answer:
3
Step-by-step explanation:
What is the first step in solving the inequality 2x + 3 ≥ 17?
The first step of solving this inequality is subtracting 3 to both sides. This will cancel 3 from the left side to start isolating x.
2x + 3 - 3 ≥ 17 - 3
2x ≥ 14
Hope this helped!
~Just a girl in love with Shawn Mendes
Answer:
x≥7
Step-by-step explanatio
To solve this problem, subtract 3 from both sides and divide by 2 from both sides.
2x+3-3≥17-3
17-3=14
2x≥14
2x/2≥14/2
14/2=7
x≥7 is the correct answer.
A case of Mountain Dew (24 cans) cost $7.68. What is the unit price?
Answer:
The answer is $0.32.
Step-by-step explanation:
You achieve this answer by taking the total price ($7.68) divided by the number of units for that price (24 cans). Therefore:
[tex]\frac{7.68}{24} = 0.32[/tex]
(-6,5)
(-3,3)
(0,1)
what are the intercepts
Answer:
(0, 1)Step-by-step explanation:
y-intercept: (0, y)
x-intercept: (x, 0)
Therefore the y-intercept is only (0, 1).
Gabe swam 2 hours each day, 5 days each week, for 5 weeks. In that time,gabe swam 1,500 laps. What was his average rate in laps per hour?
Answer:
30 laps per hour
Step-by-step explanation:
The first thing you do is calculate the amount of hours he swam for. Since he swam 2 hours each day, 5 days each week, for 5 weeks we use the equation 2*5*5. The answer is 50. After that what we do is take the amount of laps and divide it by 50. We do 1500 divided by 50 and we get a total of 30 laps per hour.
what is the middle term in the simplified product( x+3) (x-4)
Answer:
The middle term, once simplified is -x
Step-by-step explanation:
( x+3) (x-4)
FOIL
first
x*x = x^2
outer: -4*x = -4x
inner: 3*x = 3x
last: -4*3 = -12
Add them together x^2 -4x+3x-12
x^2 -x +12
When studying the population of flying squirrels, only a sample of flying squirrels population was measured. Why would just a sample be measured? Explain how this sample can be used to make an inference about the entire population of flying squirrels.
Answer:
When studying a random sample of the population, you are studying one of many (generally the same) flying squirrels that live. This small selection represents the whole population, (because as said before, they are generally the same). In this way, you can assume that the small section that you picked is going to represent the entire flying squirrel population.
1. If a, b, c, d, and e are whole numbers and a(b(c
+ d) + e) is odd, then which of the following
CANNOT be even?
(A) a
(B) b
(C)c
(D) d
Answer:
a CANNOT be even ⇒ answer A
Step-by-step explanation:
* Lets revise the rules of even and odd numbers
- Even numbers any number its unit digit is (0 , 2 , 4 , 6 , 8)
- Odd numbers any number its unit digit is (1 , 3 , 5 , 7 , 9)
# even + even = even ⇒ 2 + 4 = 6
# odd + odd = even ⇒ 1 + 3 = 4
# odd + even = odd ⇒ 1 + 2 = 3
# even × even = even ⇒ 2 × 4 = 8
# odd × odd = odd
⇒ 3 × 5 = 15
# odd × even = even ⇒ 5 × 6 = 30
∵ a[b(c + d) + e] = odd
∵ odd × odd = odd
∴ a must be odd and [b(c + d) + e] must be odd
∵ odd + even = odd
∵ odd × even = even
# Case 1
∴ b(c + d) must be odd if e even
∵ b(c + d) is odd
∴ b must be odd and (c + d) must be odd
∵ c + d must be odd
∵ odd + even = odd
∴ c or d can be even
- We now now that e , c and d can be even
# case 2
∴ b(c + d) must be even if e odd
∵ b(c + d) is even
∵ even × even = even
∴ b and (c + d) both can be even
∵ c + d can be even
∴ c or d can be even or odd
- We now now that e , c , d and b can be even
∴ Only a can not be even
* a CANNOT be even
Which of the following represents the set of possible rational roots for the
polynomial shown below?
2x^3+ 5x^ 2– 8x-10=0
Answer:
is there an option for no solution? because when I solved there were no possible rational solutions
Step-by-step explanation:
Answer:
This was the correct answer choice in my case.
Step-by-step explanation:
Hope this helps!
On a baseball field, the pitcher’s mound is 60.5 feet from home plate. During practice, a batter hits a ball 257 feet at an angle of 31° to the right of the pitcher’s mound. An outfielder catches the ball and throws it to the pitcher. Approximately how far does the outfielder throw the ball?
A. 174.2 ft
B. 183.0 ft
C. 207.5 ft
D. 147.2 ft
Answer:
Option C (207.5 feet)
Step-by-step explanation:
The questions which involve calculating the angles and the sides of a triangle either require the sine rule or the cosine rule. In this question, the two sides that are given are adjacent to each other the given angle is the included angle. This means that the angle is formed by the intersection of the lines. Therefore, cosine rule will be used to calculate the length of b. The cosine rule is:
x^2 = y^2 + z^2 - 2*y*z*cos(X).
Let x be the distance covered by the outfielder's throw, let y be the distance between the pitcher's mound and the home plate, let z be the distance covered by the batter's shot, and let X be the mentioned angle.
The question specifies that y=60.5 feet, X=31°, and z=257 feet. Plugging in the values:
x^2 = 60.5^2 + 257^2 - 2(60.5)(257)*cos(31°).
Simplifying gives:
x^2 = 43053.9184501 feet.
Taking square root on the both sides gives x = 207.5 feet (rounded to the one decimal place).
This means that the Option C is the correct choice!!!
The axis of symmetry for the graph of the function is f(x) = 1/4 x2 +
bx 10 is x = 6. what is the value of b?
Answer:
Step-by-step explanation:
f(x) = 1/4 x²+bx+10
the derivate is : f'(x) = 1/2 x +b
you have : f'(6)=0
1/2 (6)+b=0
3+b =0
b = -3
so f(x) = 1/4 x²-3x+10.......f(6) =1/4(6)² -3(6)+10 =9-18+10 =1
f(x) = 1/4(x-6)²+1... the vertex form
Value of 'b' from the quadratic function will be (-3).
Axis of symmetry of a parabola,If the quadratic equation for the parabolic path has been given as,
f(x) = ax² + bx + cAxis of symmetry of the parabola will be given by,
Axis of symmetry = [tex]-\frac{b}{2a}[/tex]
Quadratic function given in the question → [tex]f(x)=\frac{1}{4}x^2+bx+10[/tex]
Compare this equation by [tex]f(x)=ax^2+bx+c[/tex]
[tex]a=\frac{1}{4},b=b,c=10[/tex]
Axis of symmetry of the parabola will be,
Axis of symmetry = [tex]-\frac{b}{2(0.25)}[/tex]
= [tex]-2b[/tex]
Axis of symmetry has been given as x = 6,
[tex]6=-2b[/tex]
[tex]b=-3[/tex]
Therefore, value of b will be (-3).
Learn more about the quadratic function here,
https://brainly.com/question/1435393?referrer=searchResults
5(2x-3) in distributive property
Answer:
The answer is (5*2x) - (5*3)
Step-by-step explanation:
You just have to multiply the coefficient by the individual numbers and variables inside the parentheses. :)